2020
DOI: 10.1071/mf19313
|View full text |Cite
|
Sign up to set email alerts
|

Temperature dependency equation for chub mackerel (Scomber japonicus) identified by a laboratory rearing experiment and microscale analysis

Abstract: In this study, juveniles of chub mackerel (Scomber japonicus) were reared from eggs in six different temperature treatments, and their otoliths were subjected to micromilling and microvolume stable oxygen isotope (d 18 O) analysis. We determined the d 18 O values of otoliths (d 18 O otolith) formed at mean temperatures of 16.3, 17.6, 18.3, 20.0, 24.0 and 26.58C and identified a linear relationship between rearing water temperature (T, 8C) and d 18 O otolith as follows: d 18 O otolith (VPDB)-d 18 O water (VSMOW… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 22 publications
0
19
0
Order By: Relevance
“…Although previous studies reported changes in factors such as growth and maturity during the period of population decline (Watanabe and Yatsu, 2004, 2006), limited information is available for the period of population increase, especially for recent years. In addition, although much attention has been paid to the impact of environmental and endogenous factors (e.g., temperature, food availability, and age/size) on chub mackerel growth in the larval and early juvenile stages (Hunter and Kimbrell, 1980; Sassa and Tsukamoto, 2010; Kamimura et al , 2015; Higuchi et al , 2019; Kaneko et al , 2019; Taga et al , 2019; Nakamura et al , 2020), comparatively little research has been conducted on later growth stages (Parrish and Mallicoate, 1995; Watanabe and Yatsu, 2004; Yatsu et al , 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Although previous studies reported changes in factors such as growth and maturity during the period of population decline (Watanabe and Yatsu, 2004, 2006), limited information is available for the period of population increase, especially for recent years. In addition, although much attention has been paid to the impact of environmental and endogenous factors (e.g., temperature, food availability, and age/size) on chub mackerel growth in the larval and early juvenile stages (Hunter and Kimbrell, 1980; Sassa and Tsukamoto, 2010; Kamimura et al , 2015; Higuchi et al , 2019; Kaneko et al , 2019; Taga et al , 2019; Nakamura et al , 2020), comparatively little research has been conducted on later growth stages (Parrish and Mallicoate, 1995; Watanabe and Yatsu, 2004; Yatsu et al , 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the respective region should also be named as the "natal region." In addition to regional differences, the differences in δ 18 O between otoliths and water was negatively correlated with water temperature, and therefore it can be used as an indicator of ambient water temperature [25,61]. The significant differences between the populations of C. nasus in the Qiantang estuary and those in the Yellow Sea and the Changjiang estuary may mainly reflect the differences in the average water temperatures during the early life of C. nasus.…”
Section: Discussionmentioning
confidence: 99%
“…Although an otolith was originally used as a tool to estimate the age of fish [12,13], analyses of its shape and elemental/isotopic microchemistry have recently demonstrated enormous potential for its use in studies of species, population, or ecosystem-based management [14][15][16][17][18][19]. Meanwhile, otolith elemental/isotopic chemistry, also termed as otolith microchemistry, is a powerful technique for revealing migration history, population connectivity of the research object, temporal and spatial distribution characteristics (using elemental signatures) [20][21][22][23][24], dietary changes, and environmental temperature in the species' life-history using stable isotopic signatures [25][26][27][28], even with limited (e.g., 2-10) numbers of otolith samples [21,23,29].…”
Section: Introductionmentioning
confidence: 99%
“…Because it was difficult to obtain larval and juvenile chub mackerel from the field, reared samples (n = 36; FL 41-185 mm) were used. Chub mackerel were reared at the Hakatajima Station, National Research Institute of Fisheries and Environment of Inland Sea (Imabari, Japan), following the procedure reported by Nakamura et al (2020). Lenses were extracted from intact eyes.…”
Section: Lens-body Size Relationshipmentioning
confidence: 99%